2007
DOI: 10.1007/s11187-007-9082-x
|View full text |Cite
|
Sign up to set email alerts
|

Are small firms less efficient?

Abstract: Technical efficiency, SMEs, Subcontract, Switching, Metafrontier, D24, L23, L25, L26,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
81
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(98 citation statements)
references
References 41 publications
12
81
1
4
Order By: Relevance
“…This conforms to the findings of Yang and Chen (2009) and implies that, through learning over time, firms can lower their inefficiency effects. The figures for LDCs, as well as those for the overall region, were negatively correlated with the FA figures, although the correlation was not significant.…”
Section: Parameter Estimationsupporting
confidence: 90%
See 1 more Smart Citation
“…This conforms to the findings of Yang and Chen (2009) and implies that, through learning over time, firms can lower their inefficiency effects. The figures for LDCs, as well as those for the overall region, were negatively correlated with the FA figures, although the correlation was not significant.…”
Section: Parameter Estimationsupporting
confidence: 90%
“…Considering the different internal and external environmental factors for the biotechnology firms in the Asia-Pacific region, we eventually se lected the following input environmental variables: firm age (FA); the number of l abourers employed by the first 50% of the firms in the group divided by the average number of labourers employed by all firms (IMES); the industry R&D intensity (IRDI), representing t he average annual R&D density of all firms; GDP, representing a country's total value of all factors of production; and the average population density (POP), obtained by dividing the total population of a country by its land area (Dietsch and Lozano-Vivas 2000;Staikouras et al 2008;Thoraneenitiyan and Avkiran 2009;Yang and Chen 2009). Using these variables, we could identify the factors affecting the inefficiency of the environmental variables.…”
Section: Environmental Variablesmentioning
confidence: 99%
“…On the other hand, the analyses of results of the third hypothesis, show that companies with more complex production process types do not have better and more efficient operational planning. With regard to this, it can be concluded that there is no coherence between the result itself and the research by Yang and Chen (Yang & Chen, 2007). However, it must be emphasised that the coherence between the basic hypothesis of this article and previous research, point to the quality and credibility of the research.…”
Section: Discussionmentioning
confidence: 72%
“…As regards the interrelations between operational production planning and type of production process, according to Yang and Chen (Yang & Chen, 2007), the implementation of operational production planning procedure in some enterprises is achieved in easier and in others in a more difficult way. In the majority of enterprises with assembly line production type, the same product constantly passes through same working posts with capacities harmonised reciprocally.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Because of our previous experiences with micro enterprise owners [30] we offered them too chose among ranges of annual turnover instead to record precise annual turnover. We expected that annual turnover [13], [28] will depend upon characteristic of business [29], [16], [19] characteristics of the…”
Section: Data Collection and Methodologymentioning
confidence: 99%